Managing supply chains in time of crisis : an overview - Soufiane, TAIDI; Hajar, BENAYIBA (African Scientific Journal, 2021)
This paper aims to explain the management of supply chains in exceptional times mainly marked by surviving a crisis or a given risk, thus, it identifies firstly the concept of risk and risk management by a qualitative approach relying on literature review in order to highlight the role of a resilient supply chain to remedy the impact of this latter. And hence provide some clarity for today’s business to survive the current crisis due to COVID-19 pandemic.